Fontes de fibra na gestação e lactação e sua relação com a microbiota intestinal e o desempenho de matrizes suínas - Fernandes, Cátia Lidiane Alves (2021)
The gestation is considered one of the most important stages for swine production, as its performance can be reflected in subsequent stages. Nutritional strategies such as the use of functional fibers can contribute to improve the performance of sows during gestation and lactation. The aim of this study was to evaluate the inclusion of functional fiber in the diet and its impact on the intestinal microbiota, on the performance of sows and their respective litters, during gestation and lactation. Initially, 120 sows were selected, from 3 to 7 farrowing, distributed in random blocks. Sows received three diets during gestation and lactation: control treatment with 15% inclusion of soybean husk (CON), S25F treatment, control diet + 2.5% inclusion during gestation and 1.0% in lactation. partially soluble fiber and treatment (IF), control diet + inclusion of 2.5% during pregnancy and 1.0% insoluble fiber during lactation. 10 sows from each treatment were selected to evaluate blood parameters. In the 10 sows, volatile fatty acids (VFA), intestinal microbiota and pH were also evaluated in feces, at 111 days of gestation and at 16 days of lactation. At 16 days of lactation, immunoglobulins IgA and IgG were evaluated in the milk of sows. There was no significant difference between treatments regarding the performance of sows and piglets (P>0.05). At 111 days of gestation, plasma urea levels were higher in CON compared to other treatments (P<0.10). The percentage of IgG in CON milk was higher compared to S25F and IF and IgA was higher in S25F (P<0.05). The levels of acetic and isobutyric acid were higher in CON compared to the other treatments (P<0.05). In S25F, the highest abundance of the Euryarchaeota phylum was observed at 111 days of gestation (P<0.10) and at 16 days of lactation (P<0.05). At 111 days, the genus Clostridium IV and Methanobrevibacter were more abundant in S25F (P<0.10). In S25F it was also observed lower relative abundance of the genus Terrisporobacter (P<0.05). At 16 days of lactation, the relative abundances of the genus Clostridium IV and Clostridium XIVa were higher in CON (P<0.10). The genus Methanobrevibacter was observed in greater abundance in S25F at 16 days of lactation (P<0.10). It is concluded that the inclusion of functional fibers can improve the use of nutrients present in the diet, the immunological quality of milk, modulate the production of VFAs and alter the intestinal microbiota of the sows.